2004
DOI: 10.1159/000074918
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Apoptosis in Uremia Is Normalized with Continuous Blood Purification Modalities

Abstract: Uremia is associated with a state of immune dysfunction. Dysregulation of homeostasis may be directly related to abnormal apoptosis regulation in uremia, which is crucial for the maintenance of the biological system. We demonstrated that plasma from three groups of uremic subjects, i.e. hemodialysis (HD) patients, peritoneal dialysis (PD) patients and patients with predialysis chronic renal failure (CRF), has different apoptotic potential on U937 monocytes. The plasma of HD and CRF subjects when incubated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 16 publications
2
13
1
Order By: Relevance
“…This may be due to a greater accumulation of toxic factors during the acute event, as compared to patients who had a better baseline renal function. Abnormal apoptosis rates in chronic uremic patients have been previously reported by our group [18,19]. Interestingly, the plasma of CRS type 1 subjects demonstrated a stronger apoptogenic effect compared with that reported in CKD patients from our prior studies (a more than 3-fold increase).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This may be due to a greater accumulation of toxic factors during the acute event, as compared to patients who had a better baseline renal function. Abnormal apoptosis rates in chronic uremic patients have been previously reported by our group [18,19]. Interestingly, the plasma of CRS type 1 subjects demonstrated a stronger apoptogenic effect compared with that reported in CKD patients from our prior studies (a more than 3-fold increase).…”
Section: Discussionsupporting
confidence: 64%
“…The impaired cellular host defense is associated with an elevated degree of monocyte apoptosis in end-stage renal disease patients on long-term hemodialysis, CAPD, as well as those in predialytic uremia [17]. We have previously shown that uremic plasma could increase in vitro apoptosis rates in U937, a human monocytic cell line [18,19]. Recent studies have investigated the immune-modulation in the failing human heart and have shown activation of inflammatory cytokines in the myocardium and peripheral monocytes leading to monocyte phenotype transition, myocyte apoptosis, and activation of matrix metalloproteinase [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…This may indicate a higher degree of microinflammation among HD patients. These findings are in agreement with previous studies in HD and in PD patients [20][21][22] .…”
Section: Discussionsupporting
confidence: 94%
“…We have previously reported that independent of hemodialysis (HD) treatment, uremia is a state that induces apoptosis, but we have also observed that patients on peritoneal dialysis (PD) have a markedly lower rate of monocyte apoptosis -essentially similar to that in healthy volunteers [11] . The occurrence of lower apoptosis rates in PD patients leads one to postulate that the continuous purifi cation of blood and uremic apoptotic mediators with continuous PD may have a benefi cial effect compared to the intermittent accumulation in HD patients.…”
Section: Introductionmentioning
confidence: 81%